Geraniol inhibits biofilm formation of methicillin-resistant Staphylococcus aureus and increase the therapeutic effect of vancomycin in vivo - Gu, Kexin; Ouyang, Ping; Hong, Yuxin; Dai, Yuyun; Tang, Ting; He, Changliang; Shu, Gang; Liang, Xiaoxia; Tang, Huaqiao; Zhu, Ling; Xu, Zhiwen; Yin, Lizi (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is among the common drug resistant bacteria, which has gained worldwide attention due to its high drug resistance and infection rates. Biofilms produced by S. aureus are known to increase antibiotic resistance, making the treatment of S. aureus infections even more challenging. Hence, inhibition of biofilm formation has become an alternative strategy for controlling persistent infections. In this study, we evaluated the efficacy of geraniol as a treatment for MRSA biofilm infection. The results of crystal violet staining indicated that 256 μg/mL concentration of geraniol inhibited USA300 biofilm formation by 86.13% and removed mature biofilms by 49.87%. Geraniol exerted its anti-biofilm effect by influencing the major components of the MRSA biofilm structure. We found that geraniol inhibited the synthesis of major virulence factors, including staphyloxanthin and autolysins. The colony count revealed that geraniol inhibited staphyloxanthin and sensitized USA300 cells to hydrogen peroxide. Interestingly, geraniol not only reduced the release of extracellular nucleic acids but also inhibited cell autolysis. Real-time polymerase chain reaction data revealed the downregulation of genes involved in biofilm formation, which verified the results of the phenotypic analysis. Geraniol increased the effect of vancomycin in eliminating USA300 biofilms in a mouse infection model. Our findings revealed that geraniol effectively inhibits biofilm formation in vitro. Furthermore, in combination with vancomycin, geraniol can reduce the biofilm adhesion to the implant in mice. This suggests the potential of geraniol as an anti-MRSA biofilm drug and can provide a solution for the clinical treatment of biofilm infection.